Optimal Timing for Capturing Satellite Thermal Images of Asphalt Object - Sadek, Toufic Abd El-Latif; Attalah, Yousef; Faour, Ghaleb (European Scientific Journal, ESJ, 2016)
The best extraction of asphalt object from satellite thermal images is the aim of the study. The best original data of thermal images occurred at a specific times during the days of the year. by preventing the gaps in times which give the close and same brightness from different objects. Finally, to achieve easy and efficient extraction of asphalt object from the satellite thermal images and then better analysis. The study were done using seven sample objects, asphalt, concrete, metal, rock, dry soil, vegetation, and water, located at one place carefully investigated in a way that all the objects achieve the homogeneous in acquired data at same time and same weather conditions. The samples of the objects was at roof of building at position taking by global positioning system (GPS) which its geographical coordinates is: Latitude= 33Â° 37Â´ 25.402â€, longitude= 35Â° 28Â´ 57.260", height= 600 m. It has been found that the first choice and the best time for capturing the satellite thermal images for better extraction of the asphalt object in february, march, November is at 1:00 pm, in august, october at 2:00 pm and coincide with the mean. In april, may at 3:00 pm, in june at 4:00 pm and not coincide with mean. It can be noted too that the time 1:00 pm is valid in all the months and coincide with mean.